Targeting of renin-angiotensin system in COVID-19 patients affected by stroke: Emerging concerns about detrimental vs. benefit effect - Luzzi, Sabino (Interdiscip Neurosurg, 2020)
OBJECTIVE: The present short report summarizes some clinical characteristics of six patients affected by stroke while being on angiotensin-converting enzyme (ACE)2 inhibitors and angiotensin II receptor blockers (ARBs) before and during COVID-19. METHODS: Medical charts and images of six patients affected by stroke while being on ACE-Is and ARBs therapy before and during COVID-19 outbreak in Lombardy region, Italy, were reviewed. RESULTS: Three patients had a dural sinus thrombosis, whereas the remaining suffered by an arterial ischemia, which was a middle cerebral artery occlusion in one case, and a posterior-inferior cerebellar artery occlusion in the remaining two. All patients showed clinical features typical of SARS-CoV-2 infection and positive chest CT scan, and were treated with ACE-Is as needed. Hypercoagulability panel was negative in any case. A recovery was achieved in all cases, although in a variable manner. CONCLUSIONS: Whether or not and in which manner the pharmacomodulation of the renin-angiotensin system may had affect the clinical course of the reported six COVID-19 patients affected by stroke has to be still clarified. An urgent need of randomized clinical trials aimed to assess the safety profile and neuroprotective properties of ACE-Is and ARBs in COVID-19 patients diagnosed with stroke does exists.